(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
Acyclovir, an antiviral drug used against herpes simplex virus and varicella zoster virus. The dose ranges between 200 and 800 mg and the oral bioavailability is 10‑20%, which decreases as the dose is increased. The aim of this research work was to formulate and characterize nanosuspensions of acyclovir with an intention to increase the oral bioavailability. Nanosuspensions were prepared by the precipitation-ultra sonication method and the effects of important process parameters i.e., precipitation temperature, stirring speed, end point temperature of probe sonicator, energy input and sonication time were investigated systematically, the optimal nanosuspension (particle size 274 nm) was obtained at values of 4°C, 10,000 rpm, 30°C, 600 Watt and 20 min, respectively. The nanosuspension was lyophilized using different matrix formers and sucrose (100% w/w to drug) was found to prevent agglomeration and particle size upon reconstitution was found to be 353 nm. The lyophilized nanocrystals appeared flaky in scanning electron microscopy images, the X‑ray powder diffraction and differential scanning calorimetry analysis showed the nanoparticles to be in the crystalline state. Ex vivo permeation study for calculating absorption rate and in vivo bioavailability area under the curve both showed three‑fold increase over marketed suspension. Key words: Differential scanning calorimetry, ex vivo chicken intestine study, precipitation-ultra sonication, probe sonicator, scanning electron microscopy, X‑ray powder diffraction